The feasibility of worksheet based on scientific creative thinking skills and critical thinking skills for physics learning in high school - N P Mardhiah; S Feranie; P Sinaga (International Conference on Mathematics and Science Education of Universitas Pendidikan Indonesia, 2018)
This research aimed to determine the quality and comprehension of worksheet based onscientific creative thinking skills and scientific critical thinking skills. The method used in this research is research and development. The instruments used in this study consist of the test instrument of quality worksheet and the instrument of comprehension worksheet. Data analysis techniques for worksheet quality through questionnaire worksheet consisting of several aspects as much as 20 items, while data analysis for the comprehension worksheet using test of main idea the paragraph and test supporting main idea the paragraph. The result of data analysis for test of worksheet quality obtained by result of scoring of questionnaire value from three expert lecturers and 10 of physics teachers, converted in the form of percentage obtained the quality of worksheet developed by 82,5% that is in very good category. The result of data analysis for comprehension test conducted on 32 students is 87.5% in the independent category (high). The Average of quality test results and comprehension test of 85% are included in the eligible category. Thus, the feasibility of worksheet based on scientific creative thinking skills and critical thinking skills on the topic of momentum impulse is worth to using.